Leadership Role in the Formation of Students’ Morals - Yuli Supriani; Hasan Basri; Andewi Suhartini (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Kiai is one of the most essential elements in a pesantren because Kiai is a founder, pioneer, or forerunner of pesantren. Kiai is a very important component and is a central figure that regulates the continuity of a pesantren. Education in pesantren is supervised and guided directly by a pesantren leader or kiai who has a good example in himself which can be exemplified by students and kiai as well as an emphasis on morals and basics of religious knowledge. So it is clear that kiai has a major role in education in Pesantren. The purpose of this study was to find out how the role of kiai in fostering the morals of students at Pondok Pesantren Miftahul Huda 407 Sumberjaya, West Lampung. To achieve this goal, the approach used in this study is a qualitative approach with a type of qualitative descriptive research and data collection techniques using interviews and observations strengthened through documentation. The results showed that Kiai's role in fostering the morals of students included: a) Kiai as a religious figure, b) Kiai as a central figure in Pesantren, c) Kiai as a parent for students, d) Kiai as a salaried teacher, e) kiai as head of the discipline.